Pengembangan Media Pop-Up Book Digital Bermuatan Lokal Kalimantan Timur pada Materi IPAS Kelas V - Siti Mutmainah Iis Yuliani; Sukriadi; Taufik Hidayat; Iksam (Universitas Ngudi Waluyo, 2025)
Abstract The background of this research is the lack of modern and interactive learning resources that integrate technology into the learning process. As a solution, a digital Pop-Up Book about natural wealth was created for fifth-grade elementary school students in the IPAS subject. This media is based on the local wisdom of East Kalimantan. The main objective of this development is to enhance students' appreciation of local culture and make the material easier to understand. Analysis, design, development, implementation, and evaluation are the five steps in the research and development (R&D) method using the ADDIE model. The subjects of the research are fifth-grade students of SD Negeri 008 Samarinda Ilir. Data collection was conducted through observation, interviews, and questionnaires. The trial participants, including teachers, students, media experts, language experts, and content experts, were involved in the data collection process. The validation results indicate that this learning media falls into the